Assessment of Pain and Associated Factors in Female Patients Undergoing Surgical Treatment for Breast Cancer: Cross-Sectional Study - Leonardo Breno do Nascimento de Aviz; Laerte Jonatas Leray Guedes; Raphaely Cristiny Sanches Progênio; Carolina Lima da Fonte; Victória Tavares Brioso; Maikon da Silva e Silva; Laura Maria Tomazi Neves; Saul Rassy Carneiro (Revista Brasileira de Cancerologia)
Introduction: Pain is a common complication following surgical treatment for breast cancer. This symptom may result from a combination of biological, psychological, and social factors, thereby requiring a comprehensive, multidimensional approach to assessment and management. The functional impact of postoperative pain is considerable, as it can interfere with activities of daily living and compromise limb mobility. Objective: To verify the prevalence of pain, characterize it and analyze the factors associated with its intensity in patients undergoing breast cancer surgical treatment. Method: Cross-sectional study conducted between March 2021 and March 2022, in Belém, Pará, Brazil. A structured questionnaire was used to collect sociodemographic, clinical, and lifestyle data from patients in the postoperative period of breast cancer surgery. Pain was qualitatively assessed using the McGill Pain Questionnaire. Multiple linear regression was performed to identify factors associated with pain intensity, using the general pain index from the McGill instrument as the dependent variable. A 5% significance level was adopted for all statistics. Results: Forty-eight patients post-breast cancer surgery were included, the mean age was 53.64±11.64 years, 85% had undergone chemotherapy, 58.3%, mastectomy and 62.5% were feeling pain at the time of the evaluation. Pain intensity was negatively associated with alcohol consumption (p = 0.04) and positively associated with physical inactivity (p = 0.02), presence of comorbidities (p = 0.02), lymph node positivity (p = 0.03), and postoperative duration (p = 0.03). Conclusion: It was observed that most patients presented acute and moderate pain in the postoperative period and its intensity was associated with lifestyle, clinical and surgical characteristics.